Removal of mercury(ii) and methylene blue from a wastewater environment with magnetic graphene oxide: adsorption kinetics, isotherms and mechanism. Issue 86 (31st August 2016) - Guo, Yongfu; Deng, Juan; Zhu, Junyan; Zhou, Xiaoji; Bai, Renbi
Abstract : The magnetic graphene oxide (MGO) has maximum adsorption capacities of 71.3 and 306.5 mg g −1 for Hg(ii ) and methylene blue, respectively. And MGO has a magnetization of 31.5 emu g −1, easily separated from solutions via exterior magnets. Abstract : To enhance the adsorption capacity and affinity of graphene oxide (GO) for heavy metals and dyes, a magnetic graphene oxide composite (MGO) was synthesized with magnetic Fe3 O4 and graphene oxide and used to study the adsorption performance for the heavy metal Hg(ii ) and the dye methylene blue (MB). The adsorbents were characterized by XRD, FTIR, zeta potential, BET, SEM-EDS, magnetic properties, Raman and XPS analyses. Batch adsorption experiments were performed to evaluate the adsorption conditions and reusability. The results show that the as-prepared MGO had a much higher Langmuir surface area of 1259.9 m 2 g −1 . The kinetic data well fitted the pseudo-second order and intra-particle diffusion equations. The adsorption isotherm of MGO for Hg(ii ) and MB were best described by the Langmuir model with a maximum adsorption capacity of 71.3 and 306.5 mg g −1, respectively, which surpassed the adsorption capacities of many other materials. And this result was also much higher than the adsorption capacity of GO for Hg(ii ) and MB of only 32.7 and 216.7 mg g −1 . Overall the adsorption processes of Hg(ii ) and MB onto MGO were controlled by intra-particle diffusion and involved some chemisorption. The thermodynamics indicated that the adsorption process of MGO for Hg(ii ) and MB was endothermic and spontaneous in nature. Moreover, the adsorption capacity of MGO was still over 80% of the initial saturation adsorption capacity after being used five times. Lastly, we found out that the as-synthesized MGO was efficient for Hg(ii ) removal from real chloralkali wastewater. Results of this work suggest that the magnetic GO nanoparticles may be a promising adsorbent for the adsorption of heavy metals and dyes from wastewater.